Community Satisfaction Survey On "Lapak Asik Onsite" Service: BPJS Ketenagakerjaan Blitar City - Amelia Nurina Syahra; Damar Kristanto; Phima Ruthia Dwikesumasari; Edwin Fiatiano (TIJAB (The International Journal of Applied Business), 2022)
Abstract The COVID-19 pandemic has changed the old ways of doing business. Various policies are pursued so that the industry remains able to co-op in a pandemic situation and can revive the business. Likewise, government institutions are required to always be able to provide excellent service to the community and strive to maintain the quality of their services even in a pandemic condition. BPJS Ketenagakerjaan is one of the public service institutions that also strive to innovate to be able to provide the best service even in a pandemic condition. One form of strategy that is sought is the LAPAK ASIK ONSITE Services. Blitar is a diverse and growing city. The presence of LAPAK ASIK ONSITE Services can be said to be something new and the people of Blitar are still adapting to this new service model. The new strategy must be well guarded so that the implementation of LAPAK ASIK ONSITE Services in the city of Blitar can run well, be accepted by the community, and satisfy the community following the mandate carried out by the implementation of good governance, including by conducting performance evaluations through community satisfaction surveys. This study aims to measure whether LAPAK ASIK ONSITE Services have been able to provide community satisfaction. This study uses an approach to calculating the Community Satisfaction Index based on PERMENPAN RB no.14-2017. The results of this study indicate that BPJS Ketenagakerjaan in Blitar City has been able to provide good LAPAK ASIK ONSITE Services and can generate community satisfaction.